2020
DOI: 10.1002/lio2.401
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis in patients with cystic fibrosis—Current management and new treatments

Abstract: ObjectivesThe purpose of this article is to provide a state‐of‐the‐art review of the literature and summarize the latest publications on medical and surgical treatment of cystic fibrosis (CF) chronic rhinosinusitis (CRS), with an emphasis on describing recent advancements in cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies.MethodsA comprehensive literature review was conducted utilizing the PubMed database with search phrases detailed within the body of the article. Abstracts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…The heterogeneity of genetic defects leading to CF development highlights the complex nature of this disease. It was discovered that the clinical manifestation of CF is determined by the type of the mutation in the CFTR gene and that the degree of CFTR dysfunction implies clinical presentation of the disease [10,11]. Additionally, genotype appears to influence the severity of CF-related sinonasal disease and presumably may also interfere with the degree of sinus cavity development [12].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 4 more Smart Citations
“…The heterogeneity of genetic defects leading to CF development highlights the complex nature of this disease. It was discovered that the clinical manifestation of CF is determined by the type of the mutation in the CFTR gene and that the degree of CFTR dysfunction implies clinical presentation of the disease [10,11]. Additionally, genotype appears to influence the severity of CF-related sinonasal disease and presumably may also interfere with the degree of sinus cavity development [12].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Almost 90% of CF patients express at least one copy of F508del mutation. According to various authors, homozygosity for F508del was associated with more severe sinonasal disease, the presence of NPs and the higher propensity of endoscopic sinus surgery [10,11,14]. Berhout et al observed that CF individuals with class I-III mutations had significantly less developed frontal and sphenoid sinuses, higher opacification in the sinonasal area, and more frequent presence of bony sclerosis/osteoneogenesis, than those with other class mutations.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 3 more Smart Citations